Study Group Report - February 1965 Expert Sector Committee - Planning Commission (Planning Commission, 1965)
The Export Sector Committee of the Board of Trade decided at its meeting on the 5th December, 1962, to set up a number of Study Groups to carry out an intensive study of the commodities that figure in India’s export trade. One such Study Group was set up to go into the problems, relating to the following agricultural commodities :- 1. Sugar 2. Tobacco 3. Oilseeds 4. Vegetable non-essential oils 5. Oilcakes 6. Essential oils 7. Gums and Resins 8. Lac 9. Cashew kernels 10. Cocoa.
Directorate of Commercial Publicity, Ministry of Commerce